Personas en actividad. - Universidad Estatal a Distancia (San José, Costa Rica : UNED, 2024)
Aparecen Carlos Morgan, Héctor Brenes, Rodrigo Arias, Minor Herrera y Roxana Cubero
Colección Fototeca UNED
Keywords: Morgan Marín Carlos Manuel; Arias Camacho, Rodrigo; Brenes Soto, Héctor; Herrera Chavarría, Minor; Cubero Arias, Roxana; FOTOGRAFÍAS; UNIVERSIDAD ESTATAL A DISTANCIA -- COSTA RICA; FOTOTECA